Clinical Forensic Medicine A Physician's Guide - Stark, Margaret M. (Forensic Science and Medicine, 2005)
This revised edition of a much praised survey of the fundamental principles of clinical forensic medicine has been completely updated and expanded to address the latest developments and professional concerns. There are new chapters on the medical aspects of police restraint, including injuries that may occur with handcuffs and truncheons, the use of crowd-control agents, substance misuse problems in custody, and the management of bites, head injuries, and self-inflicted wounds. Additional new material can be found on the potential of police exposure to infection, the role of alcohol and drugs in vehicular accidents, and forensic sampling in sexual assault examinations. The chapters on fundamental principles, nonaccidental injury in children, and the care of detainees are all fully revised, as are the appendices (now containing a list of useful websites). Authoritative and up-to-date, Clinical Forensic Medicine: A Physician's Guide, Second Edition offers forensic specialists and allied professionals a reliable guide to good practices and procedures for every variety of police inquiry requiring clinical forensic investigation.